The Effect of Management Support on the Delivery of Devolved Services in Selected Counties in Kenya - Fauziya Brek Karama; Kavoo Linge (European Scientific Journal, ESJ, 2019)
Devolution is a tool that brings government services closer to the people. Several countries are devolving functions so as to improve service delivery, enhance governance, accountability and increase equity. Kenya embarked on an ambitious devolution program which has achieved marked degrees of success. Thus, this paper investigated effect of the management support on the delivery of devolved services in selected counties in Kenya. The study adopted a correlational analytic method targeting a population of 35,444 staff from 8 counties. A set of questionnaires were used that comprised of a population of 384 employees selected from eight counties. Structured and open-ended questionnaires were used in the study. Data analysis was done using descriptive statistics, correlation and regression analysis. Hypothesis 1(Ho1) stated that management support does not have a significant effect on the delivery of devolved services in selected counties in Kenya. Findings showed that management support had coefficients of estimate which was significant basing on β1 = 0.761 (p-value = 0.000 which is less than α = 0.05). The null hypothesis was thus rejected and it was concluded that management support had a significant effect on service delivery The study concludes that there is need for enhanced management support and supervision to the counties during project implementation because management support provides an enabling environment at the county level that facilitates effective devolved service delivery.